IMPROVING STUDENTS’ WRITING ABILITY THROUGH MAPPING TECHNIQUE - Desmalia Purba; Wisma Marbun (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2020)
This study aims at finding whether mapping technique significantly affect the students’ essay writing ability. It is Classroom Action Research (CAR) in which the subject is the second semester students of Letters Faculty of Darma Agug University. Data collection method was done in two ways because the data are in the form of qualitative and quantitative data. Based on the result of cycles implementation, it was found that the ability of students were improved from good to be better while teaching them by using mapping technique, it was from 62.85 to be 69.07. Then, in the second cycle, their score is 77.30. It can be concluded that Mapping Technique significantly affect the students’ writing ability in essay.